Улогата и развојот на зборообразувањето во проучувувањето на јазичните промени со преглед на најпродуктивните зборообразувачки процеси во англискиот јазик - Наумоска Саракинска, Билјана (Филолошки факултет, Скопје, 2019)
Language, as a system of words, is affected by numerous cultural and social influences, and, as such, is constantly changing and evolving. These changes take place over a period of time and they are, to an extent, related: they do not happen without reason, and without any consequences. For this reason, a given language undergoes significant changes during its growth and development, and not just from one period of its history to another, but, also within one and the same stadium, i.e., phase of its evolution. The reasons for the appearance, as well as the use of certain forms and constructions in a given language may well be located in a previous phase of its development; in other words, something that may have been a regular occurrence in the past may now be random and isolated, an exception to some current rule. This paper takes a look at the role and development of the discipline of word formation in connection with the study of linguistic changes and provides a brief overview and analysis of the most productive word formation processes in English.
Keywords: зборообразувачки процеси, морфологија, (нулта/регресивна) деривација, сложување, скратување, спојување